PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS VI B SD NEGERI 002 KIYAP JAYA KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Alfani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low learning outcomes in PPKn among sixth-grade students at SD Negeri 002 Kirap Jaya, as indicated by an average student score of only 62.14, which was below the minimum mastery criterion (KKM) of 65. Therefore, this study was conducted with the aim of improving students’ PPKn learning outcomes through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model. This study employed a classroom action research design consisting of the stages of planning, action implementation, observation, and reflection, and was carried out over two cycles. The subjects of the study were 40 sixth-grade students at SD Negeri 002 Kirap Jaya. The results of the research indicate a significant improvement in students’ learning outcomes, as evidenced by increased teacher and student activities as well as higher levels of learning mastery. Teacher activity improved from a score of 11 (45.83%) in Cycle I Meeting I to 14 (58.33%) in Cycle I Meeting II, increased to 19 (79.19%) in Cycle II Meeting I, and further rose to 22 (91.66%) in Cycle II Meeting II. Student activity also showed consistent improvement, increasing from a score of 10 (41.66%) in Cycle I Meeting I to 13 (54.16%) in Cycle I Meeting II, rising to 17 (70.83%) in Cycle II Meeting I, and reaching 20 (83.33%) in Cycle II Meeting II. Furthermore, students’ PPKn learning outcomes improved markedly, where at the baseline stage only 20 students (50.00%) achieved mastery in the low category, in Cycle I the number of students achieving mastery increased to 30 students (75.00%) in the high category, and in Cycle II mastery further increased to 36 students (90.00%) in the very high category.